Challenges of promotional mix towards customer decision making / Nur Hidayah Mustafa - Mustafa, Nur Hidayah (2019)
This paper aims to investigate the challenges of promotional mix towards customer decision making among Adora Travel and Tour‟s previous customers. The buyer decision making is the major concern of the marketers in influence the customers in purchasing the products or services. The buyer decision consist of the process which is of need recognition and problem awareness, information search, evaluation of alternative, purchase and post-purchase evaluation. In every stage, have the main concern from customers to the product or services that being offering. The promotional mix that consist of advertising, sales promotion and personal selling will assist the marketers in delivering the information to the customers. The advertisement can deliver the information to the customers using traditional and digital advertisement. The sales promotion can attracted the customer‟s attention towards the products by offering the monetary and non-monetary sales promotion. These strategies to gain customer‟s attention especially for short-term period and long-term period. The personal selling concern about the marketers ability in gain customer‟s trusted. The performance of the marketers will measure the first perspective of the customers towards the brans equity. The performance of the marketers also will measure the willingness of the customers to the services that being promoted. This paper will determine the relationship between relationship promotional mix which emphasize on advertisement, sales promotion and personal selling with customer decision making. This study was carried out through a survey method using questionnaires as the main instrument. Pearson correlation coefficient was used to measure the relationship between customer decision making as dependent variable and advertisement, sales promotion, personal selling as independent variables and revealed that there was a significant positive relationship between variables. Next, this paper will present the research framework, methods, measures and findings, limitation, implications and recommendation.